Anatomists’ perspective on boosting bioethics in medical education - Kumar, Dinesh; Murugan, Magi; Devi, Rema (Research and Humanities in Medical Education, 2019)
The last few decades have witnessed the emergence of the field of bioethics. Students entering medical college face unique ethically charged situations. Cadaveric dissection is one such area of ethical uncertainty. Studies have shown that an appropriate orientation towards the values inherent in a doctor’s relationship with patients, colleagues, and society might help medical students learn how to navigate ethical dilemmas they face. The aim of this article is to examine the feasibility of incorporating ethics teaching in anatomy education, and to emphasize the crucial role of professional identity in shaping the inner image of the "to-be" physician. We also discuss ways by which professional identity can be emphasized right from the 1st-year of medical school. Such endeavors may help learners find ways to respond ethically in their professional life. Understanding the role of bioethics in anatomy education with regard to professional identity formation can guide policy-makers and medical educationists.